2013
DOI: 10.4271/2013-01-0917
|View full text |Cite
|
Sign up to set email alerts
|

Post Injections for Soot Reduction in Diesel Engines: A Review of Current Understanding

Abstract: This work is a technical review of past research and a synthesis of current understanding of post injections for soot reduction in diesel engines. A post injection, which is a short injection after a longer main injection, is an in-cylinder tool to reduce engine-out soot to meet pollutant emissions standards while maintaining efficiency, and potentially to reduce or eliminate exhaust aftertreatment. A sprawling literature on post injections documents the effects of post injections on engine-out soot with varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
89
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(92 citation statements)
references
References 84 publications
3
89
0
Order By: Relevance
“…The indicated mean effective pressure (IMEP) was found in the range of 2.1 -2.6 bar for all the post injection cases, while the base case was found to be approximately 1.8 bar (due to the overall less fuel amount per cycle). The low-load, low-speed conditions of the present work are in line with the literature, where is has been suggested that such conditions are suitable for the study of soot reduction strategies since, in general, post injection is less effective as a strategy for reducing soot at higher loads (O'Connor and Musculus, 2013a). Moreover, the PPC-like operation mode is believed to have better applicability in the lower part of the engine load range, while retaining the use of conventional diesel fuel with current fuel injection equipment of passenger cars (Bakker et al, 2014).…”
Section: In-cylinder Pressure Analysissupporting
confidence: 77%
“…The indicated mean effective pressure (IMEP) was found in the range of 2.1 -2.6 bar for all the post injection cases, while the base case was found to be approximately 1.8 bar (due to the overall less fuel amount per cycle). The low-load, low-speed conditions of the present work are in line with the literature, where is has been suggested that such conditions are suitable for the study of soot reduction strategies since, in general, post injection is less effective as a strategy for reducing soot at higher loads (O'Connor and Musculus, 2013a). Moreover, the PPC-like operation mode is believed to have better applicability in the lower part of the engine load range, while retaining the use of conventional diesel fuel with current fuel injection equipment of passenger cars (Bakker et al, 2014).…”
Section: In-cylinder Pressure Analysissupporting
confidence: 77%
“…Post-injections can (re-)introduce high-temperature reactions in a region near the injector or increase local mixing again, promoting complete oxidation of the soot formed earlier [11]. The scheduling of post-injections is particularly important and seems to be hardware dependent, but reduced engine-out soot levels have been reported, without necessarily compromising on fuel economy [7]. 4.…”
Section: Introductionmentioning
confidence: 99%
“…With an optimized configuration of injection and dwell timing, injection of small quantities prior to the principal fuel delivery has been proven capable of reducing fuel consumption, particulate matter, and CO and NOx emissions in different load regimes [1][2][3][4][5]. Supplementary injections after the main delivery, known as post-injections, may significantly reduce engine-out soot and unburnt hydrocarbon (UHC) emissions [3,6], but the reported efficacies of this differ significantly [7].…”
Section: Introductionmentioning
confidence: 99%
“…A combination of ultraviolet-visible optical diagnostics was applied to the combustion chamber of a diesel engine in order to study the multiple fuel injection (Mancaruso, et al, 2008). The understanding of post injections for soot reduction in diesel engines was reviewed (O'Connor and Musculus, 2013).…”
Section: Introductionmentioning
confidence: 99%